2020
DOI: 10.1016/j.livres.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Golgi protein 73, hepatocellular carcinoma and other types of cancers

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors with a low survival rate. The identification of mechanisms underlying the development of HCC helps uncover cellular and molecular targets for the diagnosis, prevention, and treatment of HCC. Golgi protein 73 (GP73) level is upregulated in HCC patients and potentially can be a therapeutic target. Despite many studies devoted to GP73 as a marker for HCC early diagnosis, there is little discussion about the function of GP73 in HCC tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 82 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…AFP-L3 is a PHC-specific marker, mainly secreted by hepatoma cells and able to enter the blood circulation [ 12 ]. GP73 is a Golgi type II transmembrane protein, and several researchers have pointed out that its concentration in the serum of PHC patients is increased [ 14 , 23 , 28 ]. When liver cancer occurs, its cells cannot make good use of vitamin K, resulting in a decrease in the activity of vitamin K-dependent γ -glutamyl carboxylase and a decrease in the carboxylation of prothrombin precursor, thereby causing a large amount of DCP to be produced and secreted into the blood circulation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…AFP-L3 is a PHC-specific marker, mainly secreted by hepatoma cells and able to enter the blood circulation [ 12 ]. GP73 is a Golgi type II transmembrane protein, and several researchers have pointed out that its concentration in the serum of PHC patients is increased [ 14 , 23 , 28 ]. When liver cancer occurs, its cells cannot make good use of vitamin K, resulting in a decrease in the activity of vitamin K-dependent γ -glutamyl carboxylase and a decrease in the carboxylation of prothrombin precursor, thereby causing a large amount of DCP to be produced and secreted into the blood circulation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its function is incompletely understood. Golgi protein 73 expression is linked to patients with liver disease, particularly HCC ( 184 , 185 ). In the serum of HCC patients, Golgi protein 73 concentration is significantly elevated compared to patients with liver cirrhosis ( 186 ).…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%
“…In fact, it has been observed that hyperglycemia persists for 3 years after recovery from SARS(Yang et al, 2010). Apart from the role of GP73 in promoting cell proliferation, tumor development, and metastasis(Wang and Wan, 2020), GP73 also represses the host innate immune response to promote RNA virus replication(Zhang et al, 2017). Therefore, long-term follow-up of infected patients is a priority.…”
Section: Discussionmentioning
confidence: 99%